Two sides of the same coin? The effect of differentiation on noncompliance with European Union law. (March 2023) - Sczepanski, Ronja; Börzel, Tanja A
Noncompliance and differentiated integration are two strategies to cope with heterogeneity between European Union member states. This article explores the relationship between the two strategies of coping with heterogeneity. We start from the observation that research has linked cross-country variation in differentiated integration and noncompliance to similar root causes—diverging preferences and differential capacity. Addressing the same issues of heterogeneity, we hypothesize that differentiated integration is likely to reduce member states' noncompliance. In order to test this hypothesis, we combine novel data on differentiated integration and noncompliance. We find that differentiation increases rather than reduces the likelihood of noncompliance. We conclude by discussing why differentiated integration does not serve as a strategy to prevent noncompliance.